Acid Attack on Reinforced Concrete Incorporated with Industrial Wastes - R, Dhanaraj; N, Sakthieswaran (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The study was conducted to evaluate the durable characteristics of Reinforced Concrete with silica fume and copper slag. The concrete mix design was done for M40 grade concrete with 7% silica fume as cement and 10 to 30% of copper slag as sand. Also the concrete contains the total fiber content 3% of steel, basalt and Alkali Resistant Glass Fiber (ARGF). Â To study the durability characteristics such as resistance against acid, specimens were cast for different content of industrial wastes, fibers and it was compared with the control concrete.In this investigation an attempt was made in order to know the behavior of standard concrete of M40 grade specimens curing with acids such as HCl, and H2SO4 of 1% concentration at 28 days curing. Test results indicate that use of Silica fume, copper slag and fibers in concrete has improved the performance of concrete in durability aspect